Prevalence, predictors, and clinical prognosis of macrophage infiltrates in patients with ST-segment elevation myocardial infarction caused by plaque erosion as assessed by OCT. (14th October 2021) - Zhao, C; Hu, S; Weng, Z; Chen, X; Zeng, M; He, L; Feng, X; Xu, Y; Ren, X; Yu, H; Li, L; Zhang, S; et al.
Abstract: Background: Autopsy series showed that one of most common plaque phenotypes underlying coronary thrombi was plaque erosion. Identification of erosion may permit a less invasive management. Chronic inflammation is a common process in atherosclerosis. The severity of plaque inflammation can be assessed by optical coherence tomography (OCT) defined macrophages density. The impact of macrophage infiltrates (MØI) in ST-segment elevation myocardial infarction (STEMI) patients caused by plaque erosion was still unknown. Purpose: The aim of this study was to evaluate plaque morphology and clinical prognosis associated with MØI as assessed by optical coherence tomography in STEMI patients caused by plaque erosion. Methods: From October 2014 to December 2017, 1561 STEMI with OCT imaging before percutaneous coronary intervention were enrolled in this study. Finally, 312 STEMI patients caused by plaque erosion were split into two group according to the presence of MØI in culprit eroded plaques. Results: 163 (52.2%) STEMI patients presented plaque erosion with MØI, whereas 149 (47.8%) patients had no evidence of MØI. MØI were more frequency appeared in older patients (p=0.015). The severity and vulnerability of culprit lesions were higher in patients with MØI characterized by more aggressive and vulnerable features. Patients with MØI had worse long-term prognosis, compared with patient without MØI, mainly driven by a higher rate of target lesion revascularization (p=0.046), especially in STEMI patients presented plaque erosion with intensive antiplatelet therapy (p=0.035). Conclusions: In the present study, we demonstrated that macrophage infiltrates at the site of erode plaques were associated with severity and vulnerability of culprit lesions. The long-term prognosis in patients with MØI were poorer especially in patients without stent implantation. Funding Acknowledgement: Type of funding sources: None.